Leadership and governance in air route development. (September 2019) - Spasojevic, Bojana; Lohmann, Gui; Scott, Noel
Abstract: This paper examines leadership and governance among large tourism stakeholders, notably airlines, airports and state/national DMOs, in the context of air route development (ARD). An exploratory mixed method is used to identify the key leadership and governance attributes of successful ARD, and the strongest correlation among them. This study has identified a substantial difference between the key attributes perceived by small/medium enterprises (SMEs) and large tourism stakeholders. Large stakeholders identify partnership, effective communication, and information sharing as key leadership attributes, and strategic vision, leadership, and knowledge sharing as critical governance attributes. Additionally, a significant difference is observed in the correlations of attribute perception, which is dependent on the leading ARD stakeholder. Highlights: Leadership and governance attributes were identified for stakeholder engagement. Attributes correlation were measured for successful air route development process. Significant differences were identified depending on who is leading the process.